PROFIL PROGRAM KELUARGA HARAPAN (PKH) TERHADAP KESEJAHTERAAN KELUARGA DI DESA PASLATEN SATU KECAMATAN TATAPAAN KABUPATEN MINAHASA SELATAN (The Profile of â€œKeluarga Harapanâ€ Program to the Family Welfare in Paslaten Satu Village, Tatapaan, Minahasa Selatan Regency) - Serli Sengo; Noortje M. Benu; Leonardus R. Rengkung (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
This study aimed to determine the Profile of â€œProgram Keluarga Harapanâ€ (PKH-Family Hope Program) to the family welfare in Paslaten Village, Tatapaan District, South Minahasa Regency. The main objectives of theÂ PKH were to reduce numbers and break the poverty chain, to improve the quality of human resources, and to change behavior that did not support the welfare improvement of the poorest groups.The study was conducted from July to October 2019. The data used were primary data obtained through interviews with 20 (twenty) respondents of PKH recipient families and secondary data obtained from the Village Office in Paslaten. Data analysis method used was descriptive analysis.The results showed that the Family Hope Program (PKH) was greatly helped the community.Â Â Â Â Â Â Â Â Â Â Keywords: PKH, Family Hope Program, welfare.